ETNOGRAFI KOMUNIKASI DALAM TRADISI THUGUN MANDI DI DESA PELANGKO KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU PROVINSI RIAU - Maryanti, Desi; Salam, Noor Efni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Thugun mandi tradition is one of the culture that still preserved and do by Riau Community. One of the them is in Pelangko Village Kelayang District Indragiri Hulu still do the thugun mandi tradition that means take a bath for the newborn baby.This research is Qualitative research that use symbolic Interaction approach and ethnograhy communication theory that reviewing the role of language in communicative behavior in society. The informant in this research is the village shaman, indigenous stakeholders, and others public figure. The data collection technique use observation, Interview, and documentation.The result of this research showed that thugun mandi tradition that campulsony do in every newborn babyis done in Parents house and attend by the Father’s and mother’s Family also invite the community. The communicative event of thugun mandi is type event that are regards, petition, pantun and pray mantra that is spaken by shaman baby indigenous stakeholders or older people. The topic of thugun mandi is to Formalize and introduce to the community that the family members increases, to express gratitude to Allah SWT and to tighten the relationship of both familywith other community. The aim and Fungction of thugun mandi is to pray for baby to be blessing in life and to keep baby from evil spirits. The participants are the family from father, mother, colleague, the community and indigenous stake holders. The type of massage are verbal an nonverbal. The content of massage in thugun mandi event is in every process when the shaman start the event. The sequence of the events is in the begining when the baby is given a bracelet and thanksgiving event. The role of interaction is when the shaman sung the pray advice and mantra for the baby. The norm of this event is couresy norm, gather, appreciate the value and devout. The communicative act in this event is someone that lead the event should have ability, skill and understand the norm and custom value. Keywords: communicative situation, communicative events and communicative acts thugun mandi tradition